“My whole life I’ve been dressing up like a man”: Negotiations of Queer Aging and Queer Temporality in the TV Series Transparent - Linda M. Hess (European Journal of American Studies)
At a time when America is increasingly regarded as a “graying nation,” but aging LGBTQ persons often remain marginalized in discourses of aging, the TV series Transparent takes portrayals of queer aging in new directions. Transparent not only redresses this invisibility of older LGBTQ persons, but also questions heteronormative, linear understandings of life courses. The show queers the cultural constructs of aging and temporality in significant ways: by emphasizing the complex intersections of aging, sexuality, and gender identity embodied by the show’s aging transgender protagonist; by foregrounding the ways in which various members of the Pfefferman family (especially Maura’s daughter Ali) challenge linear trajectories of the life course; and by introducing, in Season 2, a narrative queering of time that interweaves the past with the present.